Association between serum vitamin D levels and visceral adipose tissue among adolescents: a cross-sectional observational study in NHANES 2011-2015 - Yan-feng Li; Xiao Zheng; Wen-lan Gao; Feng Tao; Yi Chen (BMC, 2022)
Abstract Background In recent years, obesity and vitamin D deficiency are more prevalent among adolescents. Improving our knowledge of the link between vitamin D and visceral adipose tissue (VAT) is essential for the health of adolescents. This study aimed to examine the connection between serum vitamin D levels and VAT mass among adolescents participating in the United States. Methods This is a cross-sectional study that used data from the 2011 to 2015 National Health and Nutrition Examination Survey (NHANES). The connection between serum vitamin D levels and VAT was investigated using weighted multiple linear regression models. Potential nonlinear relationships were explored using smooth curve fitting. Results The analysis included 3171 adolescents aged 12-19 years. Vitamin D levels were shown to be inversely linked with VAT in the full-adjusted model (β = − 0.34, 95% CI: − 0.49 to − 0.19). When stratified analyses by gender, this negative relationship persisted in the girls' group (β = − 0.39, 95% CI: − 0.60 to − 0.19), but not in the boys' group (β = − 0.06, 95% CI: − 0.25 to 0.13). When stratified analysis by race, this negative relationship persisted in the Mexican American group (β = − 0.61, 95% CI: − 1.03 to − 0.19), and the non-Hispanic White group (β = − 0.27, 95% CI: − 0.54 to − 0.01), but not in the other groups. Conclusions Our findings confirmed that serum vitamin D levels negatively correlated with VAT among adolescents in the United State, especially in girls, the Mexican American and non-Hispanic White. Further research is needed to determine whether increasing serum vitamin D levels decrease VAT among adolescents.